Array pattern synthesis using quadratic programming approach - Sim, Siong Leng. (2008)
This thesis reports original work on the following five areas of array processing : (i) A novel constrained optimization approach to general arrays pattern synthesis (ii) Sidelobe suppression techniques for general arrays pattern synthesis (iii) Array system in thev presence of sensor errors (iv) A new approach to broadband array pattern synthesis (v) A new approach to Generalized Sidelobe Canceller (GSC) with quiescent pattern control strategy